Molecular interaction of BMP-4, TGF-β, and estrogens in lactotrophs: Impact on the PRL promoter - Giacomini, D. (2009)
The regulatory role of estrogen, bone morphogenetic protein-4 (BMP-4), and TGF-β has a strong impact on hormone secretion, gene transcription, and cellular growth of prolactin (PRL)-producing cells. In contrast to TGF-β, BMP-4 induces the secretion of PRL in GH3 cells. Therefore, we studied the mechanism of their transcriptional regulation. Both BMP-4 and TGF-β inhibited the transcriptional activity of the estrogen receptor (ER). Estrogens had no effect on TGF-β-specific Smad protein transcriptional activity but presented a stimulatory action on the transcriptional activity of the BMP-4-specific Smads. BMP-4/estrogen cross talk was observed both on PRL hormone secretion and on the PRL promoter. This cross talk was abolished by the expression of a dominant-negative form for Smad-1 and treatment with ICI 182780 but not by point mutagenesis of the estrogen response element site within the promoter, suggesting that Smad/ER interaction might be dependent on the ER and a Smad binding element. By serial deletions of the PRL promoter, we observed that indeed a region responsive to BMP-4 is located between -2000 and -1500 bp upstream of the transcriptional start site. Chromatin immunoprecipitation confirmed Smad-4 binding to this region, and by specific mutation and gel shift assay, a Smad binding element responsible site was characterized. These results demonstrate that the different transcriptional factors involved in the Smad/ER complexes regulate their transcriptional activity in differential ways and may account for the different regulatory roles of BMP-4, TGF-β, and estrogens in PRL-producing cells. Copyright © 2009 by The Endocrine Society.